Modulation of TRPV2 by endogenous and exogenous ligands: A computational study. (22nd December 2022) - Feng, Shasha; Pumroy, Ruth A.; Protopopova, Anna D.; Moiseenkova‐Bell, Vera Y.; Im, Wonpil
Abstract: Transient receptor potential vanilloid (TRPV) channels play various important roles in human physiology. As membrane proteins, these channels are modulated by their endogenous lipid environment as the recent wealth of structural studies has revealed functional and structural lipid binding sites. Additionally, it has been shown that exogenous ligands can exchange with some of these lipids to alter channel gating. Here, we used molecular dynamics simulations to examine how one member of the TRPV family, TRPV2, interacts with endogenous lipids and the pharmacological modulator cannabidiol (CBD). By computationally reconstituting TRPV2 into a typical plasma membrane environment, which includes phospholipids, cholesterol, and phosphatidylinositol (PIP) in the inner leaflet, we showed that most of the interacting surface lipids are phospholipids without strong specificity for headgroup types. Intriguingly, we observed that the C‐terminal membrane proximal region of the channel binds preferentially to PIP lipids. We also modelled two structural lipids in the simulation: one in the vanilloid pocket and the other in the voltage sensor‐like domain (VSLD) pocket. The simulation shows that the VSLD lipid dampens the fluctuation of the VSLD residues, while the vanilloid lipid exhibits heterogeneity both in its binding pose and in its influence on protein dynamics. Addition of CBD to our simulation system led to an open selectivity filter and a structural rearrangement that includes a clockwise rotation of the ankyrin repeat domains, TRP helix, and VSLD. Together, these results reveal the interplay between endogenous lipids and an exogenous ligand and their effect on TRPV2 stability and channel gating.